Avaliação do potencial antidepressivo e mnemônico da glimepirida em camundongos submetidos a administração repetida de lipopolissacarídeo de Escherichia coli - Oliveira, Andressa Alexandre de (2021)
Depression is a prevalent disabling mood disorder that affects the patient's life quality. Currently, the monoamine theory is the most accepted one to explain depression's physiopathology. However, it cannot fully elucidate all aspects of the disease by itself. Furthermore, pharmacological treatment with available antidepressants still shows some limitations. Recent evidence suggests that inflammation can trigger depression. In this context, the use of substances with anti-inflammatory properties that are already available on the pharmaceutical market becomes relevant. Glimepiride (GLI), the most recent drug from the sulfonylurea group, showed beneficial effects against inflammation in diseases of the Central Nervous System, such as Parkinson's and Alzheimer's. However, as far as is known, there are still no studies that reveal an effect on depression. In this context, the present work aimed to investigate the potential antidepressant effect of Glimepiride in a model of systemic exposure to lipopolysaccharide (LPS) of Escherichia coli. For this, young adult male Swiss mice weighing between 20-30 grams were used. For ten consecutive days, intraperitoneal injections of LPS (0.5 mg/kg) were administered in order to induce depressive-like behavior in the animals. Between the 6th and 10th day, one hour after LPS, the animals received saline or Glimepiride (2 mg/kg) or Escitalopram (10 mg/kg) orally. Before starting treatment with Glimepiride, and on the last day of treatment, the animals' glucose levels were measured. Twenty-four hours after the last LPS administration, the animals were submitted to exploratory locomotor activity assessment and behavioral tests predictive of antidepressant effect and memory assessment. In addition, brain areas (hippocampus and prefrontal cortex) were dissected to investigate oxidative and inflammatory activities. Five-day treatment with glimepiride did not promote hypoglycemic effects in the animals. The results of the evaluation using the forced swim and tail suspension tests showed that Glimepiride had a similar antidepressant effect, reversing the depressive phenotype induced by exposure to LPS. It was evident that this effect is not related to changes in locomotor activity, considering that in the open field test, exposure to LPS or previous treatment with GLI did not influence the locomotion and exploration of the animals. Furthermore, GLI improved working memory, investigated in the Y-Labyrinth test, although it did not change recognition memory through the object recognition test. This beneficial effect of GLI on working memory is relevant considering that this parameter is generally impaired in depressed patients. Regarding neurochemical tests, Glimepiride demonstrated antioxidant activity, by decreasing MDA and nitrite/nitrate levels, in addition to increasing GSH concentrations in the prefrontal cortex. GLI also demonstrated anti-inflammatory activity, decreasing IL-1β and TNF levels in the hippocampus but not in the prefrontal cortex of mice. In short, Glimepiride showed similar antidepressant activity, and this effect may be related to the reduction of oxidative stress and neuroinflammation, and may, in the future, after confirmation with further tests, be indicated as a therapeutic option in the treatment of depression, as well as useful in patients with diabetes presenting comorbidity with depression.